“Vaidade, vaidade. Tudo é vaidade”: uma análise retórica do discurso do deputado pastor Marco Feliciano - Andrade, Guilherme Beraldo de (2015)
This research intends to reveal and discuss the rhetorical-argumentative aspects presented in the transcript speech of the politician and minister Marco Feliciano in his participation on the online program “Poder and Política”, a project held by UOL website and Folha de São Paulo newspaper. In this interview, the politician treats about polemical themes which his character has been associated with, such as homophobia and racism, taking as a basis to his statements biblical and religious texts. The understanding of the argumentative structures used by him makes it possible the study of the persuasive efficacy of his discourse. Through this perspective, the text was analyzed considering the principles of Argumentation and Rhetoric, supported on the studies of Perelman and Olbrechts-Tyteca (2005), Meyer (1994), Aristotle (2005) and Reboul (2000) who determine the argumentative aspect question presented in its construction. After a bibliographical review it was intended to determine the argumentative structures and coherence produced by the speaker in his speech. Such structures were supported by religious convictions, even in a legislative discussion environment. The analysis shows that the positions of the speaker are not technically defined, not being properly relevant the merit of the answer, but the construction of the ethos of Marco Feliciano’s public image, someone who is known for his controversial and polemical point of view. The research reveals that, even trying to have the adhesion to his beliefs, it seems that it far more important to the speaker to get the evidence of his own person than the full convincement of the audience, especially when it is considered the universal and not particular aspect of it. This way, it is verified in Marco Feliciano’s speech the construction of an ethos that guarantees him visibility, almost a personage, or, in other words, a celebrity.